18 Upgrade to defibrillator in patients receiving cardiac resynchronisation therapy pacemakers. (5th June 2017) - Monga, Shveta; Haigh, Dominic; Royan, David; Foley, Paul; Chandrasekaran, Badrinath
Abstract : Introduction: In patients with advanced cardiac failure, the choice between CRT with (CRT-D) or without a defibrillator (CRT-P), remains a contentious issue. There is insufficient evidence from randomised controlled trials and guidelines do not make any firm recommendations. This leaves room for physician discretion and has led to wide variation in worldwide practice. Study aim and basic methods: The focus of our study was to evaluate the characteristics of CRT-P patients in the real world setting and analyse how many patients with CRT-P implant required an upgrade to CRT-D in the follow-up period. This was a retrospective single centre observational study looking at 122 patients implanted with CRT from 2011 to 2015. Data was collected from patient electronic records and follow-up visits. The median follow-up duration was 2.2 (1.2–3.3) years. Data was analysed using Microsoft excel and SPSS. Results: 1. The patients implanted with CRT-P were elderly, had more advanced heart failure with multiple co-morbidities and mostly females. 2. Only 3 out of 122 patients (2.5%) were upgraded from CRT-P to CRT-D. All these patients were males, above 75 years of age with a primary prevention indication for CRT-D and had upgrade following episodes of symptomatic ventricular tachycardia (Figure 1). 3. The main cause of mortality in patients implanted with CRT-P was non-cardiac vs. cardiac (5.7% vs. 15.6%, p value<0.001). Majority of deaths in the cardiac group were due to pump failure. Only 10% of patients in this group had documented non sustained ventricular arrhythmias. Conclusion: In our study population, the number of CRT-P patients who needed upgrade with additional defibrillator was surprisingly small in medium term follow up. This implies that clinician guided selection criteria is an appropriate method of selecting patients who may not derive additional benefit from a defibrillator.